2014
DOI: 10.1037/a0037522
|View full text |Cite
|
Sign up to set email alerts
|

Control of response timing occurs during the simple reaction time interval but on-line for choice reaction time.

Abstract: The preparation of multiple element movements has been examined for decades, with no clear explanation offered for the disparate results observed. Results from 2 experiments are presented and, in conjunction with previous results, a theoretical interpretation is offered regarding the preparatory processes that occur before, during and after the reaction time (RT) interval for multiple element movements during both simple and choice RT paradigms. In Experiment 1, number of elements and timing complexity were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
6
21
0
Order By: Relevance
“…Furthermore, in contrast to the predictions of intersensory facilitation, pairing a SAS with a visual IS does not result in a further reduction in RT latency, providing additional support for a separate, faster neural pathway (Carlsen et al 2011a). Although startle trials typically produce RT latencies that are below what would be considered possible through voluntary initiation channels, recent evidence has been provided that startle trials can exhibit delayed RTs due to lowered levels of preparation (Maslovat et al 2013(Maslovat et al , 2014b. Thus, response latency alone cannot be used to differentiate between response triggering, stimulus intensity, and intersensory facilitation effects.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, in contrast to the predictions of intersensory facilitation, pairing a SAS with a visual IS does not result in a further reduction in RT latency, providing additional support for a separate, faster neural pathway (Carlsen et al 2011a). Although startle trials typically produce RT latencies that are below what would be considered possible through voluntary initiation channels, recent evidence has been provided that startle trials can exhibit delayed RTs due to lowered levels of preparation (Maslovat et al 2013(Maslovat et al , 2014b. Thus, response latency alone cannot be used to differentiate between response triggering, stimulus intensity, and intersensory facilitation effects.…”
Section: Discussionmentioning
confidence: 77%
“…Although startle trials typically produce RT latencies that are below what would be considered possible through voluntary initiation channels, recent evidence has been provided that startle trials can exhibit delayed RTs due to lowered levels of preparation (Maslovat et al. , ). Thus, response latency alone cannot be used to differentiate between response triggering, stimulus intensity, and intersensory facilitation effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…. This structure (which we call a perception action cycle [PAC]) contains a number of latency components, including First‐Action‐Latency (an analog of laboratory reaction time, e.g., Sternberg, Monsell, Knoll, & Wright, ), Between‐Action‐Latency (also known as the interkeystroke interval, e.g., Yamaguchi & Logan, ), Action‐Count (the number of actions in a sequence, which in laboratory studies is often called sequence length, e.g., Maslovat, Klapp, Jagacinski, & Franks, ), and latency to the next attentional shift (Latency‐to‐End, which is often omitted in laboratory research but which we will consider here).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been suggested that subtracting reaction time (RT) in a single task from RT in a multiple-choice condition reflects processes related to action selection (Donders, 1969). However, recent studies demonstrated that this also reflects action preparation (Bastian et al, 2003;Maslovat et al, 2014), and therefore did not sufficiently isolate the selection process. In a recent study, we investigated the complexity of action selection in young adults using the subtraction method with different task variants to isolate the action selection component .…”
Section: Introductionmentioning
confidence: 99%